PROBLEMATIKA EKSEKUSI PUTUSAN HARTA BERSAMA DI ATAS TANAH ADAT (STUDI DI DESA LEBAH SEMPAGA KECAMATAN NARMADA KABUPATEN LOMBOK BARAT) - Baiq Santi Sulistiorini (Schemata: Jurnal Pascasarjana UIN Mataram, 2019)
This study aims to determine the customary provisions of the Village of Lebah Sempaga regarding the mastery of buildings on customary land, know the legal considerations of the judges and the barriers to execution of shared property on customary land. This research is a field research using normative and sociological juridical approaches and involves judges and litigants, community leaders and traditional leaders of Lebah Sempaga Village. Data mining is done by observation, indepth interviews and documentation studies. The results of this study indicate that the customary provisions of the Lebah Sempaga Village regarding the mastery of buildings on "pauman land" are that the community only has ownership rights to the house building and does not have ownership rights to the land where the house was built. Legal considerations applied by the Panel of Judges of the Giri Menang Religion Court in deciding joint property disputes on customary land include, among others: (a) Consideration of evidence (b) Consideration of factual events (3) Consideration of legal facts. The legal basis used is Article 37 paragraph 1 of Law Number 1 of 1974 in conjunction with Article 97 of the Compilation of Islamic Law and Jurisprudence of the Supreme Court of the Republic of Indonesia Number 58 K / AG / 2015 dated January 27, 2015, that a claim for joint property on customary land can only just sued value. The obstacle in the execution of the object of joint property disputes on customary land is the difficulty to sell the disputed object because no one wants to buy the house because only the house is purchased, not the land because the land is customary land.